Evaluation of Quicklime Dose, Stirring Speed, and Reaction Time for Coal Mine Acid Water Treatment - Veza Azteria; Joko Santoso (School of Postgraduate Studies, Diponegoro Univer, 2025)
Background: If not properly managed, coal mining activities can lead to significant damage to the earth's surface. Acid water, often referred to as acid mine drainage, typically forms during both active and inactive mining operations. This study aims to determine the effectiveness of the acid mine drainage treatment process with a quicklime neutralizing agent and was carried out to assess the reuse of acid mine drainage by the community. Methods: The research was carried out by taking samples of 200 liters of acid mine water released from the mining pit. This research utilized experimental methods to determine the neutralizing dose, stirring speed, and stirring time produced from mine acid. Results: The results of the research indicate that the dose of additional lime required is 0.145 grams of quicklime for 1 liter of acid mine water. It can be interpreted that for 1 m3 of wastewater, 0.145 kg of quicklime isrequired. As a result, with a wastewater flow rate of 700 m3/hour, 101.5 kilograms of quicklime is needed per hour. Processing acid mine drainage requires rapid stirring with a minimum speed of 100 rpm by stirring all the quicklime. Conclusion: The mixing process can be optimized by increasing the length of the acid mine drainage flow when lime is added before entering the settling pond. An analysis of the physical parameters revealed that the wastewater met quality standards.